2007
DOI: 10.1097/aco.0b013e328105e0dd
|View full text |Cite
|
Sign up to set email alerts
|

Premedication of the pediatric patient – anesthesia for the uncooperative child

Abstract: The benefits and disadvantages of new and older drugs should be weighed against each other, and decisions should be made according to the requirements of surgery, ward conditions and the severity of psychologic, developmental or mental disease. Further studies for the evaluation of the anxiolytic, sedative and antipsychotic drugs are still required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0
7

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(44 citation statements)
references
References 40 publications
0
37
0
7
Order By: Relevance
“…5 Chowdhury and Vargas 3 observed in their study that at the 10th, 30th, and 40th min during the sedation procedure, a higher percentage of children who were given 0.65 mg kg À1 midazolam showed 95% or lower SpO 2 compared with children who received the combination of 25 mg kg À1 chloral hydrate with 1 mg kg À1 meperidine. When they evaluated all groups, they reported that they did not observe a period when SpO 2 dropped below 90%, and the observed period between 90 and 93% was temporary and these cases were instantly resolved with Effectiveness of premedication agents 345 repositioning of the head and neck.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…5 Chowdhury and Vargas 3 observed in their study that at the 10th, 30th, and 40th min during the sedation procedure, a higher percentage of children who were given 0.65 mg kg À1 midazolam showed 95% or lower SpO 2 compared with children who received the combination of 25 mg kg À1 chloral hydrate with 1 mg kg À1 meperidine. When they evaluated all groups, they reported that they did not observe a period when SpO 2 dropped below 90%, and the observed period between 90 and 93% was temporary and these cases were instantly resolved with Effectiveness of premedication agents 345 repositioning of the head and neck.…”
Section: Discussionmentioning
confidence: 97%
“…However, the use of midazolam may be associated with paradoxical reactions (delayed recovery, anxiety, behavioural changes, agitation), and irregular breathing patterns, skipped heartbeats, respiratory failure, and unusual or involuntary muscle movements have been observed rarely in some children. 5 Combinations of ketamine and midazolam have been stated to be among the best and safest techniques for sedoanalgesia. 6 This combination seems particularly beneficial because the elimination half-life of each agent is approximately the same.…”
Section: Introductionmentioning
confidence: 99%
“…Midazolam serves as a very common choice to achieve anxiolysis in children, adolescents and adults before anesthesia [1, 3, 4]. While children often receive relatively high doses, the standard dosage for adults, if administered po, ranges just around 7.5–15 mg [1].…”
Section: Discussionmentioning
confidence: 99%
“…The effect of pre-medication with higher or repeated doses of midazolam has been studied previously. In these studies, midazolam reduced the autonomic and hormonal responses measured as a reduction in catecholamine, cortisol, and insulin levels [30,31,32]. In contrast, N 2 O is known to have a symphaticomimetic effect [19], which could explain the significantly higher norepinephrine levels found as compared to midazolam.…”
Section: Discussionmentioning
confidence: 89%